Involutions in the Automorphism Groups of Small Sporadic Simple Groups. (28th February 2015) - Bates, Chris; Rowley, Peter; Taylor, Paul
Abstract : For each of fifteen of the sporadic finite simple groups we determine the suborbits of its automorphism group in its conjugation action upon its involutions. Representatives are obtained as words in standard generators.